Case report: Favorable efficacy of combined afatinib and anlotinib treatment in a lung adenocarcinoma patient harboring uncommon EGFR L858M/L861R mutations - He, Yueming; Wu, Yitao; He, Rongqi; Xu, Meng; Chen, Heshan; Meng, Yiran; Zheng, Liuqing; Wang, Li (Frontiers in Pharmacology, 2024)
Targeted therapy has significantly prolonged survival of non-small cell lung cancer (NSCLC) patients carrying common EGFR mutations, but the standard care for patients with rare mutations has not been well established. Here, we report a 65-year-old female diagnosed with stage ⅢC lung adenocarcinoma located in the right inferior lobe, harboring uncommon EGFR L858M/L861R mutations. Remarkably, 24 days post-treatment of afatinib and anlotinib, chest CT scans demonstrated significant shrinkage of primary lesion, indicating a partial response. Except for mild hand-foot syndrome and diarrhea, no other severe adverse symptoms were observed throughout treatment. The patient, now on combination therapy for exceeding 12 months, exhibits further decreased tumor size and a high quality of life. This case underscores the importance of precise molecular diagnosis in guiding therapeutic strategies and provides a valuable reference for clinical decision-making in EGFR-positive NSCLC cases with atypical mutations.